Liberated Colour And Form : Russian non objective art 1915-1922. - Scottish National Gallery of Modern Art, Edinburgh (Edinburgh : National Galleries of Scotland, 1978)
Bogomazov, Alexander ; Exter, Alexandra ; Kliun, Ivan ; Klucis, Gustav ; El Lissitzky ; Malevich, Kasimir ; Matyushin, Mikhail ; Miturich, Petr Vasilevich ; Popova, Liubov ; Puni, Ivan ; Rodchenko, Alexander ; Rozanova, Olga
Liberated Colour And Form : Russian non objective art 1915-1922, Scottish National Gallery of Modern Art, Edinburgh, 10 August to 10 September 1978
boek